Stabilize garnet/electrode interface via low-melting polymer layer in solid-state lithium metal battery. (10th October 2022) - Chen, Hong; Bai, Fan; Li, Yingxiang; Deng, Junwen; Liao, Shijun; Zhang, Tao
Abstract: All-solid-state lithium batteries (ASSLB) possess great potentials in constructing safer yet higher energy-density lithium batteries to substitute for current liquid lithium-ion battery, but the poor solid-solid contact at the electrode|electrolyte exerts an ultra-high interfacial resistance to the battery system which often leads to a working failure at moderate room temperature. To overcome this lithium mitigation barrier at solid interfaces to enable ASSLB working at room temperature range, a brand-new lithium salt (lithium bis(trifluoromethane sulfonimide))-polymer (polytetrahydrofuran) composite buffer layer (PPEI) was introduced to facilitate lithium ion pass between garnet-type Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) solid electrolyte(SE) and anode or cathode electrodes. The PPEI layer owns a unique glassy transition temperature near 36.7 ℃ which enables room temperature lithium conduction up to ∼10 −5  S/cm. Moreover, with simple solvent-free casting method, PPEI displayed well improved contact with lithium, lithium iron phosphate (LFP) cathode and LLZTO solid electrolyte and expanded electrochemical window up to 5.3 V vs Li + /Li. Bearing these advantages, the impedance of the assembled solid-state Li|PPEI|LLZTO|PPEI|LFP cell was decreased by more than one order of magnitude. And it can be successfully operated at 25 ℃ for more than 130 cycles, with a capacity retention surpassing 98%.